Assessing reef fish assemblage structure: how do different stereo-video techniques compare? - Watson, D.; Harvey, Euan; Fitzpatrick, B.; Langlois, T.; Shedrawi, G. (Springer-Verlag, 2010)
Quantitative sampling of benthic communities is central to a wide range of ecological research, from understanding spatial distribution and ecology to impact studies. With the need to sample deep as well as shallow regions, limited sampling capabilities of diver-based methods and the expanding footprint of human activity, there is a need for an effective system capable of classifying benthic assemblages and able to monitor potential anthropogenic impacts. Here we describe a remote system capable of collecting benthic photo-quadratsto depths of 100 m. A procedure for the classification of these images into 64 abiotic and biotic categories is also described. During a64-daysamplingprogramthatincludedsamplingatseven locations along 1,200 km of coastline that resulted in the collection of over 9,000 images, only one day of sampling was lost due to equipment malfunction, with 99.5% of points able to be classified to the taxonomic resolution required, demonstrating the reliability and accuracy of this system. Furthermore, the incorporation of differential GPS and ultra-short baseline positioning system allowed collected images to be geo-referenced to within 0.5 m. Such precision allows the system to be used in conjunction with hydroacoustic habitat mapping techniques and potentially for repeated monitoring of areas with a small spatial extent. Development of this system provides a cost-effective means of quantifying benthic assemblages over broad scales.